2013
DOI: 10.1016/j.exppara.2013.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Female biased sex-ratio in Schistosoma mansoni after exposure to an allopatric intermediate host strain of Biomphalaria glabrata

Abstract: For parasites that require multiple hosts to complete their development, the interaction with the intermediate host may have an impact on parasite transmission and development in the definitive host. The human parasite Schistosoma mansoni needs two different hosts to complete its life cycle: the freshwater snail Biomphalaria glabrata (in South America) as intermediate host and a human or rodents as final host. To investigate the influence of the host environment on life history traits in the absence of selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Parasites were used to infect sympatric and allopatric snail hosts for three generations as described in Lepesant et al . (). For RNA extraction, cDNA generation and sequencing, and comparative analysis with the tophat 2 and cufflinks , we followed Roquis et al .…”
Section: Methodsmentioning
confidence: 97%
See 3 more Smart Citations
“…Parasites were used to infect sympatric and allopatric snail hosts for three generations as described in Lepesant et al . (). For RNA extraction, cDNA generation and sequencing, and comparative analysis with the tophat 2 and cufflinks , we followed Roquis et al .…”
Section: Methodsmentioning
confidence: 97%
“…We chose to work only with female parasites, as it was previously shown that there is an increase in female cercariae production when Sm Bre develops in Bg Gua hosts (Lepesant et al . ), and also to avoid possible bias caused by gender‐specific epialleles. We selected two infected snails with a large number of sporocysts to be donators for sporocyst grafts.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gender is genetically determined (ZZ males, ZW females) but males and females can be only distinguished morphologically when they are adults. However, no obvious morphological dimorphism is observable during the larval stages (miracidia and cercariae) [1,2], so efficient larval sexing methods are critical for experimental genetics and genomics [35], and for studies of sex ratio dynamics in different parasite populations and life-stages [6,7]. Several methods have been developed to sex cercariae.…”
mentioning
confidence: 99%